1995
DOI: 10.1148/radiology.197.3.7480728
|View full text |Cite
|
Sign up to set email alerts
|

Renal perfusion: pharmacologic changes depicted with power Doppler US in an animal model.

Abstract: The power Doppler color map reflects anticipated changes in renal perfusion after alterations in blood flow by vasoactive drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Preliminary experience in an animal model has shown the ability of PD to depict changes in renal perfusion after pharmacological manipulations [44]. A consistent decrease in PD signal intensity was observed in the kidney following epinephrine-induced vasoconstriction, whereas the PD map enhanced after vasodilatation produced with administration of papaverine.…”
Section: Vascular Response To Therapymentioning
confidence: 81%
“…Preliminary experience in an animal model has shown the ability of PD to depict changes in renal perfusion after pharmacological manipulations [44]. A consistent decrease in PD signal intensity was observed in the kidney following epinephrine-induced vasoconstriction, whereas the PD map enhanced after vasodilatation produced with administration of papaverine.…”
Section: Vascular Response To Therapymentioning
confidence: 81%
“…The ability of power Doppler mode to detect changes in the number of flowing particles, and to display them as color intensity, makes this technique much better suitable than spectral Doppler to monitor serial blood flow changes being able to evaluate a large area with many renal vessels. Durick et al [23] reported changes in renal perfusion after pharmacologic manipulations in pigs: a consistent decrease in power Doppler intensity signal was observed in the kidney following epinephrine-induced vasoconstriction, whereas the power Doppler map enhanced after vasodilatation produced with administration of papaverine.…”
Section: Physiologic Studiesmentioning
confidence: 92%
“…In contrast, the energy from the reflected echo amplitude depends mainly on the number of red blood cells within one pixel, regardless of flow and thus frequency shift direction [2±4]. Durick et al [5], in an animal model, demonstrated that vasoconstrictive agents and vasodilatory agents alter renal cortical perfusion as demonstrated by differences in the cortical blush on ACD, supporting the hypothesis that the cortical blush depends on the number of scatterers.…”
Section: Main Clinical Applicationsmentioning
confidence: 99%